Achievement Motivation and its Relationship to Critical Thinking among Nursing Students in the Kingdom of Saudi Arabia - Alatawi, Abeer; Almater, Latifah A.; Rezq, Khulud Ahmad; Salem, Raneen (Journal of Ecohumanism, 2024)
The study aimed to identify Achievement Motivation and its Relationship to critical thinking among nursing students in the Kingdom of Saudi Arabia. The research sample consisted of 200 male and female students from the College of Nursing in the Kingdom of Saudi Arabia. The researchers used the descriptive approach and the results of the study reached: Summary of the results of the first question: It turns out that the degree of availability of the level of motivation among female nursing students in the Kingdom of Saudi Arabia was (very high), as the general average was (4.5381), with a standard deviation of (.19607). The degree of evaluation of the study dimensions was arranged according to the highest arithmetic mean as follows: 1. The scope and clarity of the goal was rated very high, with an arithmetic average of (4.54). 2. The field of ambition level dimension was rated very high, with an arithmetic average of (4.5478). 3. The domain of perseverance dimension was rated very high, with an arithmetic average of (4.4972) .4. The field of perceived efficiency dimension was rated very high, with an arithmetic average of (4.5294). and It is clear from the level of critical thinking skills among female nursing students in the Kingdom of Saudi Arabia was (very high), as the general average for the second axis was (4.5570), with a standard deviation of (.19470). The degree of evaluation of the study dimensions was arranged according to the highest arithmetic mean as follows: 1. The skill of making predictions dimension was rated very high, with an arithmetic average of (4.5625( 2. The skill of interpretation dimension was rated very high, with an arithmetic average of (4.5680). 3. The skill of evaluating arguments dimension came with a very high rating, with an arithmetic average of (4.5137( 4. The skill of deduction dimension was rated very high, with an arithmetic average of (4.5430). 5. The skill of reasoning dimension came with a very high rating, with an arithmetic average of (4.5900). and It shows that there is a statistically significant correlation between the degree of availability of achievement motivation and critical thinking among nursing students in the Kingdom of Saudi Arabia at a significance level of less than (0.05), and the correlation coefficient was equal to (.336**), which is a high positive value. It indicates the existence of a strong positive relationship between achievement motivation and critical thinking.